Implementation of Information Commission Regulation Number 1 of 2013 on Public Information Dispute Resolution Procedures(Study at the Bengkulu Provincial Information Commission in 2025): Implementasi Peraturan Komisi Informasi Nomor 1 Tahun 2013 tentang Prosedur Penyelesaian Sengketa Informasi Publik(Studi pada Komisi Informasi Provinsi Bengkulu Tahun 2025) - Rayhan Saifullah; Heru Purnawan; Henny Aprianty (Gayaku Publisher, 2026)
This study analyzes the implementation of Information Commission Regulation Number 1 of 2013 on public information dispute resolution procedures at the Bengkulu Provincial Information Commission in 2025 and identifies applicants' lack of seriousness and bad faith. This descriptive qualitative study used interviews, observation, documentation and triangulation. The findings show that the procedure has been implemented through registration, preliminary examination, mediation, non-litigation adjudication, and decisions. However, substantive effectiveness is still limited by applicants' absence, incomplete documents, premature requests, overly broad requests, unclear purposes, and misuse of dispute mechanisms. Based on Ripley and Franklin's model, policy success depends not only on institutional compliance, but also on applicants' procedural understanding, seriousness, and good faith.